Testing three models in international economics: The Purchasing Power Parity Model, the Interest Rate Parity Model and the Monetary Model: The case of the Turkish Lira and the US Dollar (1975-1999) - Aleksandar Vasilev; Plamen Pavlov; Stefan Rainov; Tsvetoslav Kovatchev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2002)
The goal of this empirical project is to test the validity of three economic models – The General Monetary, The Purchasing Power Parity and The Interest Rate Parity models in Turkey – basing on quarterly data for the period 1975 – 1999. The project takes into account the serious economic shocks that hit the Turkish economy in 1979 and 1994. Different models are created and the variables are tested for Significance, Serial Correlation, Unit Root and Cointegration. The tests used throughout the project are: Dickey Fuller, Augmented Dickey Fuller, Breusch-Godfrey LM Test for cointegration and Johansen Test. The outputs of the tests are presented to support the conclusions made throughout the test. The basic findings made are that for Turkey the three models: The General Monetary Model, The Purchasing Power Parity Model and The Interest Rate Parity hold for the time period 1975 – 1999.
Keywords: F41; C32; 330; purchasing power parity; interest rate parity